Organizational Performance Consequences of Age Diversity: Inspecting the Role of Diversity‐Friendly HR Policies and Top Managers' Negative Age Stereotypes. (27th February 2013) - Kunze, Florian; Boehm, Stephan; Bruch, Heike
Abstract This paper seeks to advance the diversity literature by investigating organizational performance consequences of age diversity. Drawing from social‐identity and social‐categorization theory, we theoretically argue that, in age‐diverse companies, age‐based subgrouping processes occur, favouring a shared perception of a negative age‐discrimination climate. This perceived negative age‐discrimination climate in turn negatively relates to organizational performance. As the main contribution, top managers' negative age‐related stereotypes and diversity‐friendly HR policies are introduced as organizational‐level moderators that increase and attenuate, respectively, the social categorization processes affecting performance in age‐diverse companies. We utilized structural equation modelling (SEM) to test the proposed hypotheses using a multisource dataset comprising 147 companies. The results supported all hypotheses, indicating that low negative top managers' age stereotypes as well as high diversity‐friendly HR policies are potential organizational factors that can prevent the negative relation of age diversity with organizational performance transmitted through the negative age‐discrimination climate. These results are discussed in light of their contribution to the diversity literature and social‐categorization theory as well as their implication for practitioners.